A phase I/II trial of reduced intensity allogeneic hematopoietic cell transplant for hematologic malignancies using cladribine, thiotepa and rabbit antithymocyte globulin. Issue 8 (August 2013) - Larsen, Jeremy T.; Hogan, William J.; Micallef, Ivana N.; Dispenzieri, Angela; Gertz, Morie A.; Inwards, David J.; Tun, Han W.; Roy, Vivek; Geyer, Susan M.; Allred, Jacob B.; Wu, Wenting; Ansell, Stephen M.; et al.
Abstract We conducted a phase I/II trial to assess the efficacy of cladribine, thiotepa and antithymocyte globulin as a reduced-intensity conditioning regimen for refractory or high-risk hematologic malignancy. The preparative regimen consisted of cladribine 5 mg/m2/day for 5 days, thiotepa 200 mg/m2/day for 3 days and ATG 3 mg/kg/day (day − 5) followed by allogeneic peripheral blood stem cell transplant. Twelve patients were transplanted from a human leukocyte antigen (HLA) matched family member. Two patients were treated at dose level I but both experienced grade IV dose limiting toxicities, and therefore the thiotepa dose was reduced to 133 mg/m2/day (dose level II). Only two of the next six patients experienced dose limiting toxicities. Median age was 46 years. At dose level II, the median time to neutrophil and platelet engraftment was 17 and 20 days, respectively. The incidence of acute and chronic graft-versus-host disease (GVHD) was 40% and 30%, respectively. Day + 100 non-relapse mortality was 0% and at 1 year was 20%. Median overall survival (OS) was 42 months and 2-year OS was 70%. Median progression-free survival (PFS) was 11 months and 2-year PFS was 40%. We conclude that the reduced-intensity conditioning regimen of cladribine, thiotepa and ATG achieved excellent donor chimerism with acceptable toxicity.